Understanding Women’s Horrors in Refugee Camps through Silence is My Mother Tongue - Tara Prasad Adhikari (OUSL Journal)
The study on “Understanding Women's Horrors in Refugee Camps through Silence is My Mother Tongue” explores the psychological and social challenges faced by women refugees in refugee camps worldwide. Using a semi fictional narrative from Silence is My Mother Tongue by Sulaiman Addonia, this study examines the mental health impacts of displacement and the compounded marginalization of refugee women in patriarchal societies. It addresses key thematic issues such as identity construction, resilience, gender-based violence, female autonomy and social protection. This paper also critically reviews human rights frameworks and the role of humanitarian agencies in addressing the needs of female refugees. The study emphasizes the importance of gender-sensitive policies and aims to contribute to the ongoing discourse on gender justice for displaced women. Using a literary research paradigm, the paper discusses how refugee women navigate their experiences in the camps offering insight into the broader implications for policy and humanitarian practice.